A Patient with MSUD: Acute Management with Sodium Phenylacetate/Sodium Benzoate and Sodium Phenylbutyrate. (15th May 2017) - Köse, Melis; Canda, Ebru; Kagnici, Mehtap; Uçar, Sema Kalkan; Çoker, Mahmut
Abstract : In treatment of metabolic imbalances caused by maple syrup urine disease (MSUD), peritoneal dialysis, and hemofiltration, pharmacological treatments for elimination of toxic metabolites can be used in addition to basic dietary modifications. Therapy with sodium phenylacetate/benzoate or sodium phenylbutyrate (NaPB) in urea-cycle disorder cases has been associated with a reduction in branched-chain amino acid (BCAA) concentrations when the patients are on adequate dietary protein intake. Moreover, NaPB in treatment of MSUD patients is also associated with reduction of BCAA levels in a limited number of cases. However, there are not enough studies in the literature about application and efficacy of this treatment. Our case report sets an example of an alternative treatment's efficacy when extracorporeal procedures are not available due to technical difficulties during attack period of the disease.